Sedimentology of marine Cretaceous sequences of ODP Holes 122-762C and 122-763C - Exon, Neville F; Borella, Peter E; Ito, Makoto (Supplement to: Exon, NF et al. (1992): Sedimentology of marine Cretaceous sequences in the central Exmouth Plateau (Northwest Australia). In: von Rad, U; Haq, BU; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 122, 233-257, https://doi.org/10.2973/odp.proc.sr.122.144.1992, 1992)
Sites 762 and 763 were both drilled on the central Exmouth Plateau in water depths of about 1380 m. At Site 763, 1036 m were drilled about 100 km northeast of the Cuvier Abyssal Plain, and at Site 762, 940 m were drilled about 80 km to the north of Site 763. At both sites we recovered continuous core from fairly complete Cenozoic and Cretaceous sequences; the Cretaceous sequence is 790 m thick in Site 763 and 385 m thick in Site 762. Site 763 has an expanded Early Cretaceous sequence, and Site 762 has an expanded Late Cretaceous sequence. The Cretaceous sequence rests either on a very condensed Jurassic shelf sequence or on Triassic sediments. It commences with Berriasian deltaic mudstone and sandstone (Barrow Group) which built rapidly northward. After late Valanginian breakup of Gondwanaland, there was a hiatus before Hauterivian to early Aptian marine mudstone (Muderong Shale) was deposited following a marine transgression. A late Aptian hiatus was followed by deposition of Albian mudstone and marl (Gearle Siltstone) and late Albian to Coniacian marl (Haycock Marl). Pure pelagic carbonate sedimentation started in the Santonian (Toolonga Calcilutite), and the remainder of the Cretaceous consists of chalks. Sedimentation rates in the Berriasian were about 150 m/m.y. near Site 763 and less to the north. In the remainder of the Cretaceous they seldom exceeded 20 m/m.y. Both tectonic events and eustatic sea-level changes are reflected in the sediments. Color cycles in the marls and chalks can be related to the Milankovitch orbital precession (21 k.y.) and obliquity (41 k.y.) cycles.